PERLINDUNGAN HUKUM TERHADAP KONSUMEN YANG DIRUGIKAN AKIBAT PEMBATALAN SEPIHAK TRANSAKSI JUAL BELI OLEH PT SHOPEE INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (KASUS: IBU MAYA DI TAHUN 2018) - Verren Andreas; Mariske Myeke Tampi (Fakultas Hukum Universitas Tarumanagara, 2020)
Conventional buying and selling transactions have updated online buying and selling transactions, ranging from transactions between business actors and consumers from direct transactions to indirect transactions. Shopee is an online buying and selling site that is starting to develop in Indonesia. Consumers have rights that have been guaranteed by Shopee and the Government through laws or electronic contracts, but cases of consumers who are harmed still repeatedly occur in these electronic transactions. The formulation of the problem in this update is legal protection for consumers who suffer losses due to the cancellation of unilateral buying and selling transactions by PT Shopee Indonesia based on Law Number 8 of 1999 concerning Consumer Protection. The author in answering these problems uses normative legal research methods. The type of material that the author uses is primary data, secondary data, namely interview data and tertiary data. The results of the research on consumers who were harmed due to the unilateral cancellation of online buying and selling because Law Number 8 of 1999 concerning Consumer Protection has not clearly processed purchases virtually or online.